Neobyčejná společenstva motýlů na rašeliništích Třeboňska: přežívání reliktních populací - Jaroš, Josef , 1953-; Spitzer, Karel , 1939-
Boreal peatlands of the Třeboň Basin (South Bohemia) contain many distinctive taxa of Lepidoptera, including tyrphobionts and tyrphophiles. These ancient peatlands are oligotrophic and acidic, and form habitat islands – relict ecosystems related to subarctic/ boreal biomes. They host isolated populations of cold-adapted Lepidoptera, some of them associated with common bo - real plants. For instance, larvae of several relict boreal and subarctic moths (e.g. Eupi - thecia gelidata) feed exclusively on the lo - cal Marsh Labrador Tea (Ledum palustre). Josef Jaroš, Karel Spitzer.